An Insidious Cardiac Sarcoma Presenting with Progressive Neurologic Dysfunction - Pasalic, Dario (PAGEPress Publications, Pavia, Italy, 2013)
Central nervous system metastases as the presentation of primary cardiac sarcoma are a very rare entity, with only a few previously reported cases. Sarcomas specifically make up 10 to 20% of all primary cardiac tumors. Patients with primary cardiac tumors typically present with cardiac symptomatology that may include arrhythmias, obstruction to blood flow and valve function, or symptoms of heart failure. We report a unique case of a patient with a primary cardiac sarcoma who presented with progressive neurologic dysfunction secondary to brain metastases without any preceding cardiac symptoms. We describe our novel management of these unique cases and discuss the current medical and surgical approaches to treating neurologic metastases from cardiac sarcoma.